The Evaluation of The Effectiveness of Integrated Surgical Scheduling Implementation on Patient Waiting Time at The Urology Outpatient Clinic - Ananda Rizki Febria Michiels; Sonya Dewi Wulandari; Enrico Adhitya Rinaldi (CV. Inara, 2026)
Patient waiting time is one of the key indicators in assessing the quality of hospital services, particularly in specialized services that require operative procedures such as urology care. The increasing number of urology patients that is not supported by an integrated surgical scheduling system may lead to service delays, operational inefficiencies, and decreased patient satisfaction. This study aims to evaluate the effectiveness of integrated surgical scheduling implementation in reducing patient waiting time at the Urology Clinic of RSUD dr. Drajat Prawiranegara Serang Indonesia. This study employed a descriptive qualitative design with an evaluative approach. Data were collected through in-depth interviews, direct observations, and document reviews related to the scheduling and delivery of urology services. Informants were selected using purposive sampling and included urologists, nurses, administrative staff, and hospital management personnel directly involved in the surgical scheduling process. Data analysis was conducted thematically through data reduction, data presentation, and conclusion drawing, supported by source and method triangulation to ensure data validity. The findings indicate that the implementation of an integrated surgical scheduling system improved coordination among service units, enhanced the operational flow of surgical services, and contributed to a reduction in patient waiting time at the Urology Clinic. However, the effectiveness of the system has not yet been fully optimized due to limitations in supporting infrastructure, incomplete integration of hospital information systems, and varying levels of human resource readiness in operating digital scheduling systems. In conclusion, integrated surgical scheduling is an effective managerial strategy to improve service efficiency and the quality of urology care. System optimization requires strong managerial commitment, enhancement of health information technology infrastructure, and continuous capacity building of human resources.